The Complexity of Health Service Integration: A Review of Reviews - Heyeres, Marion; McCalman, Janya; Tsey, Komla; Kinchin, Irina (Frontiers in Public Health, 2016)
Background: The aim of health service integration is to provide a sustainable and integrated health system that better meets the needs of the end user. Yet definitions of health service integration, methods for integrating health services and expected outcomes are varied. This review was commissioned by Queensland Health, the government department responsible for health service delivery in Queensland, Australia, to inform efforts to integrate their mental health services. This review reports on the characteristics, reported outcomes, and design quality of studies included in systematic reviews of health service integration research. Method: The review was developed by systematically searching nine electronic databases to find peer-reviewed Australian and international systematic reviews with a focus on health service integration. Reviews were included if they were in the English language and published between 2000 and 2015. A standardised assessment tool was used to analyse the study design quality of included reviews. Data relating to the integration types, methods and reported outcomes of integration were synthesised. Results: Seventeen publications met the inclusion criteria. Eleven (65%) reviews were published during the past five years, which may indicate a trend for increased awareness of the need for service integration. The majority of reviews were published by researchers in the UK (8/47%), USA (3/18%), and Australia (3/18%). Included reviews focused on a variety of integration types, including integrated care pathways, governance models, integration of interventions, collaborative/ integrated care models, and integration of different types of healthcare. Most (53%) of reviews reported on the cost-effectiveness of service integration, e.g. positive results, no effect, or inconclusive. Only one of the reviews reported on the importance of consumer involvement. The overall design of 70% of the reviews was high, 18% medium, and 12% low. Conclusion: There is no ‘one size fits all’ approach to health service integration. Instead, this literature review highlighted the complexity of service integration, which in most primary studies involved a range of strategies. Rigorous assessments of cost effectiveness and reporting on consumer involvement is required in future research.